Evidence for SIRT1 Mediated HMGB1 Release From Kidney Cells in the Early Stages of Hemorrhagic Shock - Xu, Siqi; Zeng, Zhenhua; Zhao, Ming; Huang, Qiaobing; Gao, Youguang; Dai, Xingui; Lu, Jiayin; Huang, Weiqing; Zhao, Keseng (Frontiers in Physiology, 2019)
Background: This study is to explore the effect of SIRT1 deacetylating inactivation on organ-derived high mobility group box 1 (HMGB1) during the development of severe hemorrhagic shock (HS). Methods: HS model was reproduced in rats by blood shedding and mimicked in HK-2 cells by hypoxia-reoxygenation (H/R) treatment. The level and acetylation of HMGB1 and the expression and activity of SIRT1 were detected in tissue, serum and cultured cells and supernatant. The deacetylated sites of HMGB1 was determined by Co-IP. Results: Serum HMGB1 in HS rats was increased but were reduced in multiple organs, especially in kidney tissue, with enhanced HMGB1 acetylation and reduced deacetylase SIRT1 activity in isolated renal tubular epithelial cells (RTECs). HMGB1 in suspension of H/R-treated HK-2 cells was increased, accompanying with enhanced HMGB1 acetylation and nuclear-plasma translocation. SIRT1 down-regulated by siRNA aggravated acetylation of HMGB1 and nucleus-to-cytoplasm translocation and resulted in increased HMGB1 in cultured HK-2 suspension. Immunoprecipitation data suggested that SIRT1-indcuced deacetylated sites of HMGB1 were K90 and K177 following H/R. SIRT1 overexpression inhibited the acetylation of HMGB1 and reduced the content of extracellular HMGB1 in H/R-treated HK-2 cells. Inhibiting mutation of SIRT1 restored the acetylation of HMGB1 and HMGB1 content in extracellular suspension. In HS rat model, the neutralization of HMGB1 with antibody could reduce serum HMGB1 and pro-inflammatory cytokine contents, but had no effect on SIRT1 protein expression and activity. Polydatin, a potential SIRT1 agonist, up-regulated SIRT1 activity and inhibited nucleus-to-cytoplasm translocation of HMGB1 in RTECs. Moreover, polydatin also attenuated RTEC apoptosis, protected renal function, and prolonged survival in HS rats. These beneficial effect of polydatin is largely blocked by specific inhibition of SIRT1 with Ex527. Conclusions: The acetylation of HMGB1 in K99 and K177 is enhanced during HS due to the downregulation of SIRT1. The nucleus-to-cytoplasm translocation and the release of acetylated HMGB1 from RTECs of kidney might exacerbate the pro-inflammatory effects of HMGB1 during the development of HS.